Sympathy for the Devil: Belief in Satan and Moral Beliefs. Issue 5 (4th May 2023) - Desmond, Scott A.; Clark, Tom; Bader, Christopher D.
ABSTRACT: Previous research suggests that religious service attendance, biblical literalism, images of God, and other measures of religion are related to moral beliefs (i.e., that certain behaviors are wrong or deviant). Given previous theory and research on spiritual appraisals (particularly demonization and desecration), we argue that belief in Satan should also predict moral beliefs. Using the first four waves of the Baylor Religion Survey, we tested the association between belief in Satan and belief in the wrongfulness of twelve different behaviors related to abortion, family matters, sexuality, and substance use. Although religious service attendance and biblical literalism were consistently related to moral beliefs, belief in Satan was significantly related to six of the twelve moral beliefs. Furthermore, there was a significant interaction effect between religious service attendance and belief in Satan for ten of the twelve moral beliefs, suggesting that religious service attendance has little or no effect on moral beliefs when people do not also believe in Satan.